Landscape 100: How Finland, Estonia and Latvia Used Landscape in Celebrating their Centenary Anniversaries - Anu Printsmann; Hannu Linkola; Anita Zariņa; Margarita Vološina; Maunu Häyrynen; Hannes Palang (De Gruyter, 2022)
In the aftermath of what was then the Great War several European countries like Finland, Estonia and Latvia gained independence, marking their centenary jubilees 2017–2018. This paper observes how landscapes were used in anniversary celebrations and what historical themes were foregrounded and which omitted, revealing how collective historical commemoration in landscape enacts within national identity framework depending also on how landscape is understood in each respective country.